Dietary Protein, Protein to Carbohydrate Ratio and Subsequent Changes in Lipid Profile after a 3-Year Follow-Up: Tehran Lipid and Glucose Study. - Zahra Bahadoran; Parvin Mirmiran; Firoozeh Hosseini-Esfahabni; Mahboobeh Sadeghi; Fereidoun Azizi (Tehran University of Medical Sciences, 2013)
Data regarding the effects of dietary protein on modifying serum lipid and lipoprotein levels are controversial. In this study we have investigated the hypothesis whether dietary protein and protein to carbohydrate ratio could be related to subsequent changes in lipid profile in adults.This 3-yaers follow-up_longitudinal study was conducted on a sample of participants (845 men and 1043 women, aged 19-70 years) of the Tehran Lipid and Glucose Study. Dietary intakes were assessed using a validated semi-quantitative food frequency questionnaire. Anthropometric and serum lipid and lipoprotein levels were measured both at baseline (2006-2008) and after 3 years.After adjustment for potential confounding variables and dietary factors, the highest quartile energy intakes from protein was inversely associated with changes in total cholesterol (β= -6.5; 95% CI= -11.5, -1.5) and HDL-C levels (β= -6.7; 95% CI= -12.2, -1.4) in men during the follow-up. Increased proportion of energy intake from protein, compared to that of carbohydrate also had favorable effect on 3-years changes in triglycerides (β= -18.2; 95% CI= -36.7, -0.1) and total cholesterol (β= -8.4; 95% CI= -15.1, -1.8) in men. Higher dietary P/C ratio (median ≥ 0.23) was associated with a significant decrease in serum total cholesterol at 3-years follow-up in men with the higher intake of protein (median ≥ 13.4 % of energy).Higher intakes of dietary protein and more importantly, higher proportion of energy intakes from protein, compared to carbohydrate, had favorable effects on modifying lipid levels during a 3-year follow-up.